Hyper-Consumption to Circular Economy in the United Arab Emirates: Discarding the Disposable and Cherishing the Valuable - Lusk, Jeniece (2020)
Overconsumption of resources and consumer items is an important driver for environmental degradation and climate change. Malls, shopping, and conspicuous consumption are deeply ingrained in the local values and the global image of the United Arab Emirates (UAE). The UAE has a diverse and international population with over 85% expats and numerous opportunities to reduce environmental impact. Increased participation in a circular economy that aims to reduce resource use by recycling materials, reusing products, extending their lifespan, and maintaining their economic value would be an effective strategy to reduce negative environmental impacts. However, little is known about how much and why UAE citizens and residents participate in the circular economy. Therefore, it is important to examine the factors that predict participation in the circular economy in the UAE. To investigate this question, we surveyed n=163 undergraduate students at an American-curriculum university in the UAE and explored literature-based explanations as predictors for participation in the circular economy, namely gender, nationality, exposure to circular economy initiatives, efforts to reduce ecological footprints, and sustainable consumer behaviors using index-based negative binomial regression models. We also compare differences in ways and levels of participation in the circular economy between UAE citizens and residents with t-tests. Our results suggest that participation in the circular economy does not emerge from concerted efforts to reduce environmental degradation such as lowering ecological footprint and reducing waste, but rather investments in sustainable and durable items. Emirati citizens are more likely to participate in the circular economy, in particular repairing items, than expat residents. These differences are most likely to be explained by the more stable lifestyles of Emirati citizens as opposed to the more itinerant lifestyles of expat residents.